Changes in Social Work Practice in China during the COVID-19 Pandemic. Issue 5 (20th October 2021) - Wang, Lifang
Abstract : During COVID-19 pandemic, the environment for social work practice was changeable and uncertain in China. This article draws on the author's experience as a social work academic, discussing the changes that took place in social work practice which can be explored from the two aspects - that of 'front stage' and 'backstage'. At front stage, the service mode of Interdisciplinary Remote Networking (IRN) was created. It had proved to be an effective mode in linking various resources as well as taking care of the client from the biopsychosocial perspective. When compared with ordinary social work practice, it has had significance for the interdisciplinary cooperation in medical social work. In these special contexts, immediate response and comfort to the client were very important to prevent the occurrence of extreme desperation. At the backstage, the online connection of supervisors to social workers was established, which was beneficial for social workers to manage their own stress and adapt social intervention to the client experiencing COVID-19. Social workers had never been so pressingly in need of being heard than ever before. It could be concluded that humanistic care such as listening, empathy and company were common needs of both service users and social workers.